Experimental Challenge of Chinook Salmon ( Oncorhynchus tshawytscha ) With Tenacibaculum maritimum and Tenacibaculum dicentrarchi Fulfils Koch's Postulates - Karthiga Kumanan; Jeremy Carson; Ryan B. J. Hunter; Anne Rolton; Ulla von Ammon; Chaya Bandaranayake; Connie Angelucci; Richard N. Morrison; Seumas P. Walker; Jane E. Symonds; Kate S. Hutson (Journal of Fish Diseases, 2025)
The bacterial skin disease tenacibaculosis, caused by Tenacibaculum species, affects numerous economically important marine fish, including salmonids. This study reports the ability of three Tenacibaculum maritimum strains, belonging to different molecular O‐AGC types, and a single Tenacibaculum dicentrarchi strain to induce tenacibaculosis in farmed Chinook salmon ( Oncorhynchus tshawytscha , Walbaum 1792) in Aotearoa New Zealand. Naïve Chinook salmon were exposed to T. maritimum (2 × 10 8 cells/mL) and T. dicentrarchi (2 × 10 7 cells/mL) by immersion using natural seawater. Clinical signs of tenacibaculosis were apparent in all T. maritimum strains used in the challenged fish. Of these, 100% of the fish challenged with O‐AGC Type 2‐1 and Type 3‐2 strains became moribund, whereas only 60% of the O‐AGC Type 3‐0 challenged fish became moribund. Fish exposed to T. dicentrarchi showed more severe symptoms, exposing musculature in 51% of the challenged population, with 28% of fish becoming moribund. Gross pathological signs of fin rot, scale loss, skin ulcers and haemorrhagic skin spots were observed for both Tenacibaculum species and were consistent with those observed on farmed fish. Pure T. maritimum and T. dicentrarchi cultures were reisolated from epidermal damage of challenged fish. Tenacibaculum species was not isolated from the anterior kidney of affected fish, which indicates no systemic infection in Chinook salmon.